Konstribusi Kemampuan Mengapresiasi Cerpen dengan Kemampuan Menulis Cerpen Siswa Kelas XI SMAN 16 Padang - Hernanda, Andri; Abdurahman, Abdurahman; Ratna, Ellya (Universitas Negeri Padang, 2013)
TheÂ purposes of this study were to (1) describe, able to apreciation short story class XI Senior hight school 16 Padang, (2) describe, capable to write short story class XI Senior hight school 16 Padang, (3) the analities contribute able to apresiation short story to capable write short story class XI Senior hight school 16 Padang. The data this studi of were two kind test, is objective and write test. Objective test use for colleted able data student in the appreciation short story.The principle research conclude three case. First, capable appreciation short story student class XI senior hight school 16 Padang qualification at qualification moreb than enough (72,77). Second capable write short storyÂ student class XI senior hight school 16 Padang at qualification well (78,89).Third,able appreciation short story contribute to capable write short story student class XI senior hight school 16 Padang as big as 25%, and more influence by factor other not research in this research.